Pembacaan Tradisi Makan terhadap 1 Korintus 11:17-34 dan Implikasinya bagi Tradisi Mukbang - Saputra, Jefri Andri (STT Internasional Harvest Tangerang, 2024)
The purposeof this study is to address the various impact if the “mukbang” phenomenon. “Mukbang” often leads to ethical breaches in eating, promotes unhealthy dietary habits, and results in significant food waste. Additionally, there is a troubling disparity, as Broadcast Jockey (BJ) squander food while many people face food shortages and hunger. To develop a proper understanding of eating, the author references 1 Corinthians 11:17-34. The research method used is tradition criticism, focusing on eating traditions in the Old and New Testament texts. The findings suggest that “mukbang” should be grounded in the essential purpose of food, which is to sustain life. This principle should underpin healthy eating habits and emphasize the importance of sharing food in “mukbang” broadcast.